2009
DOI: 10.1253/circj.cj-09-0164
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Valve Replacement in Adult Patients With a Severely Dilated Right Ventricle and Refractory Arrhythmias After Repair of Tetralogy of Fallot

Abstract: Background: Refractory arrhythmias caused by right ventricular (RV) volume overload resulting from pulmonary regurgitation are the main concern in adult patients after repair of tetralogy of Fallot (TOF). Early pulmonary valve replacement (PVR) may prevent irreversible RV dysfunction and refractory arrhythmias, so the present study evaluated the PVR outcomes in adult patients with a severely dilated RV (d-RV) and refractory arrhythmias after TOF repair. Methods and Results: Three TOF patients with a d-RV and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Some studies however had limited improvement in survival rate and incidences of ventricular tachycardia [4,5]. Progressive fibrosis is suspected to play a pathological role in development of ventricular arrhythmias on long-term follow-up after primary repair [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies however had limited improvement in survival rate and incidences of ventricular tachycardia [4,5]. Progressive fibrosis is suspected to play a pathological role in development of ventricular arrhythmias on long-term follow-up after primary repair [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The right ventricle does, however, not always completely recover following late pulmonary valve replacement with sustained risk of refractory arrhythmia and RV dysfunction [4,5]. The cellular mechanisms of the reverse remodelling process are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…PVR was performed in 5 patients, which resulted in complete control of tachyarrhythmia in 2 patients and partial control of tachyarrhythmia in 3 patients with severe RV dilatation. 15 At the end of follow-up, 20 of 21 patients (95%) required AADs even after other effective treatments. Among 3 patients with failed control of tachyarrhythmia, 1 died suddenly, 1 died from heart failure, and 1 died from sepsis.…”
Section: Treatment For Tachyarrhythmiamentioning
confidence: 98%
“…With advancements in PVR technology, it is widely accepted to perform PVR before irreversible RV dilatation and heart function deterioration occurs in patients with rTOF [9][10][11]. Previous studies have shown that the cumulative incidence of long-term reoperation in patients with rTOF is 44%, with a median of 24 years after the initial repair [12,13].…”
Section: Preoperative Clinical Featuresmentioning
confidence: 99%